An Assessment Method for Debris Flow Dam Formation in Taiwan (2018)
Debris flows in tributaries rush into and block the main branches of rivers and often result in serious hazards. Dam failures cause large floods in the downstream area and can lead to fatalities and property damage. This study proposes an assessment method to evaluate the formation of a debris flow dam, which includes two conditions: (1) the sediment transported by the debris flow must reach across the river; and (2) the thickness of the deposit by the debris flow must be higher than the in situ water depth. This methodology was used to study the case of a debris flow dam caused by debris flow across the Er River in Taiwan, which blocked the Chishan River and led to the formation of the Namasha debris flow dam. This methodology can also be applied to identify the formation of debris flow dams.